2000
DOI: 10.1149/1.1393620
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Iron-Substituted Lithium Nickelate

Abstract: Lamellar phases with nominal composition Li(Ni 1Ϫy Fe y )O 2 (y Յ 0.30) were synthesized and characterized by Rietveld refinement of their X-ray diffraction (XRD) patterns. These materials exhibited the formula Li 1Ϫz (Ni 1Ϫy Fe y ) 1ϩz O 2 with 0.06 Յ z Յ 0.08 and were used as positive electrodes in lithium batteries. Their electrochemical performances decreased with increasing iron content. The Li x (Ni 0.90 Fe 0.10 ) 1.06 O 2 phases were characterized by XRD and Mössbauer spectroscopy. A solid solution appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 44 publications
10
51
0
1
Order By: Relevance
“…Figure 9 shows the variations of the populations of the various iron oxidation states for the Li V (Ni Fe Co ) O system compared to that obtained for the Li V (Ni Fe ) O system reported in a previous study (9). In the two systems, the general evolutions of the populations are quite similar in that they occur in several steps.…”
Section: * the Isomer Shift Ismentioning
confidence: 58%
See 2 more Smart Citations
“…Figure 9 shows the variations of the populations of the various iron oxidation states for the Li V (Ni Fe Co ) O system compared to that obtained for the Li V (Ni Fe ) O system reported in a previous study (9). In the two systems, the general evolutions of the populations are quite similar in that they occur in several steps.…”
Section: * the Isomer Shift Ismentioning
confidence: 58%
“…Conversely, the presence of the larger iron ions in the vicinity of the nickel ions leads to an expansion of the [NiO ] octahedra, making the nickel ion's oxidation more di$cult than in the Li V NiO system. As a result, a simultaneous oxidation of nickel and iron ions is experimentally observed (9,37,38 Fe ) O system for compositions with x'0.50. This observation proves that, in the "rst part of the charge, cobalt substitution favors in the same proportion the oxidation of both iron and nickel ions.…”
Section: * the Isomer Shift Ismentioning
confidence: 83%
See 1 more Smart Citation
“…ions from entering the Li sites and leads to the formation of Li 1-z (Ni 1-y Co y ) 1?z O 2 with z = nearly zero, resulting in better electrochemical properties. Prado et al [47] reported that the substitution of Fe for Ni in LiNiO 2 degrades the electrochemical properties, by making the lattice size larger and thus making the Ni 2? ions more stable than Ni 3?…”
Section: Methodsmentioning
confidence: 99%
“…However, it has some disadvantages such as nonstoichiometry (called cation mixing), degradation of the retention capacity due to a structural change during the cycling [1], and thermal instability at a highly oxidized state. Partial substitution of other elements (Co, Mn, Fe, Al, Zr, and Ti) for Ni sites has been studied to improve the electrochemical performance of LiNiO 2 [2][3][4][5][6][7][8]. Of these elements, cobalt has attracted much attention because only cobalt substitution can form a complete solid solution, and the solid solution shows better thermal stability than pristine LiNiO 2 .…”
Section: Introductionmentioning
confidence: 99%